Lebanon 2014 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Lebanon (IMF Staff Country Reports, 2014)
KEY ISSUES Context: The economy is being severely tested by the Syria crisis. The refugee influx has reached one quarter of the population, fueling already high unemployment and poverty. The political impasse from the presidential elections-following months of negotiations over a new government-adds to the uncertainty. The economy is meanwhile suffering from a broad-based deterioration, with subdued growth and widening fiscal imbalances. Public debt is on the rise. Progress on structural reforms has been limited. On the positive side, deposit inflows have held up and foreign exchange reserves are sizeable; and security conditions have significantly improved, lifting tourism prospects. Key challenges: There is an urgent need for fiscal adjustment to achieve a sustainable debt reduction, and structural reforms to boost growth and address social inequities. Key policy recommendations: • Fiscal policy.